TRENDS OF ECONOMIC RELATIONS TRANSFORMATION IN CONTEXT OF DIGITAL ECONOMY (ON THE EXAMPLE OF COMMERCIAL BANKS AND BUSINESS SECTOR) - Elena Igorevna Generalnitskaia (Science and Innovation Center Publishing House, 2019)
Background: The article presents the results of the study of digital transformation trends of economic relations between credit organizations and organizations of the business sector due to their significance for stable growth of Russian economy. Ongoing changes identified in this article as trends require thorough study in order to increase the efficiency of economic relations between credit organizations and organizations of the business sector.